Bioatenuação da geração de sulfeto, por meio da utilização de nitrato, em água produzida proveniente da extração de petróleo - Segui, Paula Nonato (2009)
In systems and industrial processes, including processes of wastewater treatment and oil exploration and production systems, the sulfide generation and the corrosion influenced by microrganisms bring countless losses worldwide. The oil industry has been engaged in developing new technologies for produced water treatment, generated in exploration processes, in order to minimize the biocorrosion in ducts and metallic materials, and also possible environmental damage. The group of microrganisms known as sulfate reducing microrganisms (SRM) has as main feature the reduction of sulfate to sulfide in the anaerobic degradation of organic matter. Besides the ecological significance in the cycle of sulfur and carbon, the SRM are related to microbiological corrosion and the generation of odors, and the oil industry is one of the most affected by the activity of this group of microorganisms. The nitrate is a cheaper alternative in relation to the biocides, commonly used in the treatment of production water, and does not offer environmental risks. The present study evaluated the use of nitrate to reduce the generation of sulfide by sulfate reducing microrganisms in samples of production water, provided by Petrobras. The experiment was designed using treatments involving three levels of nitrate, two levels of acetate (presence and absence) and three repetitions, with controls of production water, production water + slugde and production water + sludge + acetate totaling 27 experimental units. The results showed that the nitrate concentration in the intermediate level (500 mg/L) was sufficient to stop the generation of sulfide by sulfate reducing bacteria, in a period between 3 and 4 weeks after the beginning of the experiment. Moreover, the statistical analysis of data, included the samples that had the addition of acetate as an increase of the carbon source at the same group of average than the same samples, but without the addition of acetate